PENDAMPINGAN PSIKOLOGIS BAGI REMAJA KOMUNITAS ORANG DENGAN AUTOIMUN (KOMUNITAS ODAI) - Denrich Suryadi; Shakira Novel; Shafa Karina (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2021)
Autoimmune disease is condition arising from an abnormal immune response to a functioning body part/system. Immune system disorders lead to underactivity or abnormal overactivity of the immune system. From various studies that have been carried out on various patients suffering from autoimmune diseases, ranging from stress, various impacts in the form of psychological disorders to psychological well-being is an important issue for them. Those with autoimmune disease will experience various and complex physical and psychological problems and also face challenges of minimal treatment they need to receive due to limited funds, time or support from family and closest people. Personal life demands are also diverse, coupled with the challenges of late adolescent developmental tasks towards early adulthood, namely the search for self-identity and intimacy. Limited physical conditions due to immune vulnerabilities will hinder the activities and productivity of adolescents who are in their peak period of exploring various possibilities for their future. On the one hand, their mental health conditions can be disrupted due to physical limitations due to autoimmune, but on the other hand, they really need to maintain their mental health to prevent their autoimmune relapse. The program provides psychological assistance for adolescents with Autoimmune in form of individual counseling sessions in October-November 2021. The total number of participants for this period was 9 teenagers with various types of autoimmune and problems. Most problems they had are parent-child relationship issue, interpersonal skills, academic problems, Borderline Personality Disorder, Anxiety Disorder, Depression, self-harm behavior, and physical health complaints.Penyakit autoimun adalah kondisi yang timbul dari respon imun yang abnormal terhadap bagian/sistem tubuh yang berfungsi. Gangguan sistem kekebalan menyebabkan kurangnya aktivitas atau aktivitas berlebihan yang tidak normal dari sistem kekebalan tubuh. Dari berbagai penelitian yang telah dilakukan terhadap berbagai pasien yang menderita penyakit autoimun, mulai dari stres, berbagai dampak berupa gangguan psikologis hingga kesejahteraan psikologis menjadi isu penting bagi mereka. Penyandang penyakit autoimun akan mengalami berbagai masalah fisik dan psikologis yang kompleks dan juga menghadapi tantangan pengobatan minimal yang harus mereka terima karena keterbatasan dana, waktu atau dukungan dari keluarga dan orang terdekat. Tuntutan kehidupan pribadi juga beragam, ditambah dengan tantangan tugas perkembangan remaja akhir menuju dewasa awal, yaitu pencarian identitas diri dan keintiman. Kondisi fisik yang terbatas akibat daya tahan tubuh yang lemah akan menghambat aktivitas dan produktivitas remaja yang sedang berada pada masa puncaknya dalam menjajaki berbagai kemungkinan untuk masa depannya. Di satu sisi, kondisi kesehatan mental mereka dapat terganggu karena keterbatasan fisik akibat autoimun, tetapi di sisi lain, mereka sangat perlu menjaga kesehatan mentalnya untuk mencegah kekambuhan autoimun mereka. Program tersebut memberikan pendampingan psikologis bagi remaja dengan Autoimun berupa sesi konseling individu pada Oktober-November 2021. Total peserta periode ini adalah 9 remaja dengan berbagai jenis autoimun dan masalah. Sebagian besar masalah yang mereka hadapi adalah masalah hubungan orang tua-anak, keterampilan interpersonal, masalah akademik, Borderline Personality Disorder, Anxiety Disorder, Depresi, perilaku menyakiti diri sendiri, dan keluhan kesehatan fisik.